An Energy-Efficient Programmable Mixed-Signal Accelerator for Machine Learning Algorithms - Kang, M. (IEEE Explore, 2020)
We propose PROMISE, the ﬁrst end-to-end design of a PROgrammable MIxedSignal accElerator from Instruction Set Architecture to high-level language compiler for acceleration of diverse machine learning algorithms by exploiting the advantage of the superior energy efﬁciency from analog/mixed-signal processing.